In vitro mechanistic studies and potential health benefits of a standardized bilberry extract in low mood and cognitive enhancement - Kara, Mehtap; Hasbal-Celikok, Gozde; Wilson, Jacob; Gómez-Serranillos, Pilar; Yilmaz-Ozden, Tugba; Öztas, Ezgi; Özhan, Gul; Zengin, Özge Sultan; Gómez-Serranillos, Marta Sánchez; Owsianik, Claudia; Rabbani, Fazle; Tunç, Merve; et al. (Frontiers in Nutrition, 2025)
BackgroundLow mood and cognitive impairments are multifactorial conditions often linked to oxidative stress, neurotransmitter imbalances, and neuroinflammation. Bilberry (Vaccinium myrtillus L.) extract, particularly rich in anthocyanins, has shown promising neuropharmacological properties in recent studies.Aims of the studyThis study aimed to comprehensively evaluate the biochemical, antioxidant, and neuroprotective properties of a standardized bilberry extract (Mirtoselect™), alongside assessing its potential health benefits on mood and cognitive enhancement in a clinical setting.MethodsIn vitro assays were conducted to explore the neuromodulatory, antioxidant, and cytoprotective properties of Bilberry extract. Enzyme inhibition assays targeted γ-Aminobutyric acid transaminase (GABA-T), monoamine oxidase A (MAO-A), and acetylcholinesterase (AChE), while GABAA receptor binding was also evaluated. Antioxidant capacity was assessed using DPPH, ABTS, FRAP, ORAC, HORAC, and TAS assays. Neuroprotection was investigated using SH-SY5Y cells exposed to H2O2, assessing cell viability (MTT), membrane integrity (LDH release), and BDNF expression. Cytotoxicity was determined through the MTT assay in SH-SY5Y cells. A randomized, double-blind, placebo-controlled pilot clinical study was conducted on healthy adult subjects (n = 33) (aged 25–55 years) to evaluate the effects of Bilberry extract on mood (POMS) and cognitive function.ResultsBilberry extract demonstrated significant inhibition of GABA-T, MAO-A, and AChE, alongside moderate GABAA receptor binding. It exhibited robust antioxidant activity in DPPH (EC50: 9.24 ± 0.22 μg/mL), ABTS (EC50: 12.70 ± 0.11 μg/mL), FRAP, ORAC, HORAC, and TAS assays. Neuroprotective effects included enhanced cell viability, reduced LDH release, and upregulation of BDNF in SH-SY5Y cells under oxidative stress. Cytotoxicity tests confirmed a favorable safety profile. In the pilot study, Bilberry extract supplementation significantly improved mood parameters, including reduced tension, depression, and confusion scores (p < 0.05) compared to placebo, with minimal adverse effects.ConclusionBilberry extract exhibits potent antioxidant, neuromodulatory, and neuroprotective properties, supporting its potential as a natural intervention for managing low mood and cognitive health. The favorable safety profile and preliminary clinical benefits warrant further research.